2020
DOI: 10.3389/fendo.2020.595448
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Anti-Müllerian Hormone and In Vitro Fertilization-Embryo Transfer in Clinical Pregnancy

Abstract: ObjectivesTo retrospectively analyze the correlation between anti-Müllerian hormone (AMH) and the number of oocytes obtained by controlled ovarian hyperstimulation (COH) in women of different ages and explore the factors affecting in vitro fertilization and embryo transfer (IVF-ET) in clinical pregnancy of infertile women to provide evidence for infertile women to choose assisted reproduction strategies.MethodsInfertile women who received IVF-ET or intracytoplasmic sperm injection and embryo transfer (ICSI-ET)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…Besides, our work reveals that the E 2 level on the HCG day (NMIV = 0.951) ranks in second place among all impact features, which matches with the finding that the number of oocytes retrieved increases with the amount of E 2 level on the HCG day [ 29 ], as this feature somehow measures the response of the ovary to the COS and thus indirectly reflects the quality and quantity of the oocyte [ 31 ]. What is more, the NMIV of age is −0.354, meaning that age has a significant effect on the oocyte retrieving No, and the older the woman is, the more difficult it is to retrieve more oocytes in general [ 10 ]. Regarding the AMH, although recent studies claimed it has the highest importance for the ovarian response [ 32 , 33 ], our work confirmed its importance, and the larger the AMH is, the more oocytes it could retrieve in general; however, the status of AMH is weaker as compared to the AFC, E 2 level on the HCG day, and the age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, our work reveals that the E 2 level on the HCG day (NMIV = 0.951) ranks in second place among all impact features, which matches with the finding that the number of oocytes retrieved increases with the amount of E 2 level on the HCG day [ 29 ], as this feature somehow measures the response of the ovary to the COS and thus indirectly reflects the quality and quantity of the oocyte [ 31 ]. What is more, the NMIV of age is −0.354, meaning that age has a significant effect on the oocyte retrieving No, and the older the woman is, the more difficult it is to retrieve more oocytes in general [ 10 ]. Regarding the AMH, although recent studies claimed it has the highest importance for the ovarian response [ 32 , 33 ], our work confirmed its importance, and the larger the AMH is, the more oocytes it could retrieve in general; however, the status of AMH is weaker as compared to the AFC, E 2 level on the HCG day, and the age.…”
Section: Discussionmentioning
confidence: 99%
“…Poor ovarian response leads to a high risk of treatment cycles being canceled or a lack of high-quality embryos for transfer. Studies have demonstrated that the impact features, e.g., a women’s clinical information (age, body mass index (BMI), infertility cause, and infertility duration), basal endocrine level (Anti-Müllerian hormone (AMH), basal follicle stimulating hormone (bFSH)), and ultrasound-related index (antral follicle count (AFC)), are closely related to the extent of ovarian response to COS [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. The features, such as age, AMH, bFSH, and AFC, etc., are currently recognized as high-impact features related to ovarian reserve function [ 10 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, AMH has been used to assess ovarian reserve parameters and response to gonadotrophin stimulation, reproductive outcomes of infertile women [ 4 , 7 10 ]. AMH is an emerging and one of the strongest markers of NOR during IVF cycles [ 9 , 11 , 12 ]. Recent studies indicated that AMH could also independently predict pregnancy outcomes [ 13 – 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…AMH, a paracrine factor implicated in the regulation of early follicular growth, is now widely been used as a quantitative marker of ovarian reserve to predict the response to ovarian stimulation [4,5]. Meanwhile, the recent development of automated AMH assays improved the accuracy and consistency of AMH testing among different in vitro fertilization (IVF) centers [6,7].…”
Section: Introductionmentioning
confidence: 99%